Heat Storm - Castle, Richard (Kingswell, 2017)
Nikki Heat and Derrick Storm team up for the first time to save Nikki's mother, Cynthia, who has been in hiding (and presumed dead) for 17 years. Standing in their way is a nefarious group of Chinese businessmen known as the Shanghai Seven, who have the resources-and ruthlessness-to stop them.